Disasters and kidney care: pitfalls and solutions - TUĞLULAR, ZÜBEYDE SERHAN (My University, 2023)
Patients with kidney disease, especially those with kidney failure, are particularly susceptible to the adverse effects of disasters because their survival depends on functional infrastructure, advanced technology, the availability of specific drugs and well-trained medical personnel. The risk of poor outcomes across the entire spectrum of patients with kidney diseases (acute kidney injury, chronic kidney disease and kidney failure on dialysis or with a functioning transplant) increases as a result of disaster-related logistical challenges. Patients who are displaced face even more complex problems owing to additional threats that arise during travel and after reaching their new location. Overall, risks may be mitigated by pre-disaster preparedness and training. Emergency kidney disaster responses depend on the type and severity of the disaster and include medical and/or surgical treatment of injuries, treatment of mental health conditions, appropriate diet and logistical interventions. After a disaster, patients should be evaluated for problems that were not detected during the event, including those that may have developed as a result of the disaster. A retrospective review of the disaster response is vital to prevent future mistakes. Important ethical concerns include fair distribution of limited resources and limiting harm. Patients with kidney disease, their care-givers, health-care providers and authorities should be trained to respond to the medical and logistical problems that occur during disasters to improve outcomes.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY